The mind-brain relationship - Pally, Regina; Olds, David; Solms, Mark (H. Karnac (Books), 2000)
The purpose of this collection of articles, which originally appeared as a series in the International Journal of Psycho-Analysis, is to provide psychoanalysts and psychotherapists with the basic, fundamental scientific concepts of neurobiology that are relevant to clinical work with patients. In each article, whenever possible, Pally points out the clinical implications of the scientific data. The usefulness of neuroscience, neuroanatomy, and physiology rests not in specific facts but in the main principles they illustrate, neuroscientific concepts that address important questions psychotherapists and psychoanalysts face regularly in their work.
International journal of psychoanalysis key papers series
Keywords: paměť; neurovědy; psychoanalýza; mozek; Psychoanalysis; Memory; psychologie, klinická psychologie; Brain